2017
DOI: 10.1590/1678-4685-gmb-2016-0225
|View full text |Cite
|
Sign up to set email alerts
|

Is a non-synonymous SNP in the HvAACT1 coding region associated with acidic soil tolerance in barley?

Abstract: The barley HvAACT1 gene codes for a citrate transporter associated with tolerance to acidic soil. In this report, we describe a single nucleotide polymorphism (SNP) in the HvAACT1 coding region that was detected as T-1,198 (in genotypes with lower root growth on acidic soil) or G-1,198 (greater root growth) and resulted in a single amino acid change (L/V-172). Molecular dynamic analysis predicted that HvAACT1 proteins with L or V-172 were stable, although the substitution led to structural changes within the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(58 reference statements)
0
2
0
2
Order By: Relevance
“…To determine the structural similarity of TaPIMA1 to other MATE transporters in plants, we performed phylogenetic analysis of TaPIMA1 and 24 other MATE proteins from wheat, rice, Hordeum vulgare , Triticum urartu , Setaria viridis , Brachypodium distachyon , Sorghum bicolor , Arabidopsis , Arachis hypogaea , Gossypium hirsutum , Medicago truncatula , and Vitis vinifera ( Figure 2 C, Table S1 ). These 24 known-function MATE proteins encompass all the reported functions of the MATE transporters, such as disease resistance [ 38 , 39 , 40 , 49 , 50 , 51 , 52 , 53 , 54 ], aluminum tolerance [ 41 , 42 , 55 , 56 , 57 , 58 , 59 , 60 ], iron translocation [ 56 , 61 , 62 , 63 ], anthocyanidin transport [ 47 , 64 , 65 ], and heavy metals detoxification [ 43 , 44 , 66 ]. As a result, the dendrogram showed that these 25 MATE proteins were mainly clustered into two clades.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the structural similarity of TaPIMA1 to other MATE transporters in plants, we performed phylogenetic analysis of TaPIMA1 and 24 other MATE proteins from wheat, rice, Hordeum vulgare , Triticum urartu , Setaria viridis , Brachypodium distachyon , Sorghum bicolor , Arabidopsis , Arachis hypogaea , Gossypium hirsutum , Medicago truncatula , and Vitis vinifera ( Figure 2 C, Table S1 ). These 24 known-function MATE proteins encompass all the reported functions of the MATE transporters, such as disease resistance [ 38 , 39 , 40 , 49 , 50 , 51 , 52 , 53 , 54 ], aluminum tolerance [ 41 , 42 , 55 , 56 , 57 , 58 , 59 , 60 ], iron translocation [ 56 , 61 , 62 , 63 ], anthocyanidin transport [ 47 , 64 , 65 ], and heavy metals detoxification [ 43 , 44 , 66 ]. As a result, the dendrogram showed that these 25 MATE proteins were mainly clustered into two clades.…”
Section: Resultsmentioning
confidence: 99%
“…First, the expression of Al-tolerant genes increased with the copy number of genes in the genome ( Daspute et al, 2017 ). Second, the transposon insertion at the front end of the Al-tolerant gene, i.e., insertion of the transposon could be used as the promoter of the subsequent gene and enhanced the expression of the subsequent gene ( Ferreira et al, 2017 ). Third, the tandem repeats in the promoter region enhanced the expression level of resistance genes ( Ryan et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Для определения наличия или отсутствия данных мутаций у сортов ячменя были разработаны соответствующие ПЦР-маркеры. Маркеры 1kb-insertion и HvMATE-21indel в настоящий момент являются стандартными генспецифичными маркерами алюмоустойчивости, наиболее подходящими для отбора требуемых генотипов [29,30]. В исследованиях отмечается, что по точности определения фенотипической изменчивости HvMATE-21indel превосходит маркеры Bmag353 и Bmac310 на 10-20%.…”
unclassified
“…В исследованиях отмечается, что по точности определения фенотипической изменчивости HvMATE-21indel превосходит маркеры Bmag353 и Bmac310 на 10-20%. [28,29] Однако хотя SNP-1,198 и коррелирует с алюмоустойчивостью сортов ячменя, было выявлено, что он играет менее важную роль в проявлении признака по сравнению с мутациями 1kb-insertion и HvMATE-21indel [30,31].…”
unclassified